PENINGKATAN MINAT DAN HASIL BELAJAR APRESIASI SENI RUPA MELALUI PENGGUNAAN MODEL PEMBELAJARAN QUANTUM TEACHING SISWA KELAS VIII-5 SMPN 32 PADANG - Yessy Yulandari, Drs. Eswendi, M.Pd., Dra. Zubaidah, M.Pd. (Serupa The Journal of Art Education, 2017)
The purposes of this study were to (1) increase the interst of art appreciation learning through the use of learning model of quantum teaching students of class VIII-5 SMPN 32 Padang, (2) Improve the learning achievement of art appreciation through the use of quantum teaching odel of students of class VIII-5 SMPN 32 Padang. This classroom action research is carried out collaboratively with the subject teachers of Cultural Arts. The source of this research is teachers and students. Collected by test and observation techniques. Research findings is the cycle I got 72% with enough category, after the improvement of learning by reseacrhers/teachers in cycle II, then there is an increase in student learning interest to 86% with very good category. As well as art learning appreciation results that show significant improvement. This can be illustrated on the average pre cycle I, students ability continues to show a very significant increase in cycle II with an average of 93. Based on the findings of the above research it can be concluded that the teaching model of quantum teaching can increase interest and learning achievement of art appreciation of class VIII-5 SMPN 32 Padang.Key words : Interst, Learning Outcomes, Quantum teaching learning model